Reverse Transfer of Writing Rhetorical Structures by Indonesian EFL Learners - Rusfandi, Rusfandi (Soegijapranata Catholic University, 2024)
The reverse transfer of writing knowledge from L2 to L1 involves reusing and reshaping prior knowledge. However, research on this issue generally focuses on the former rather than the latter. Further investigation is needed to understand how individual (writing and language proficiency) and social factors (writing audience) interact dynamically during L2 and L1 writing and affect the reverse transfer. This study investigates the potential transfer of rhetorical structures from L2 English to L1 Indonesian as a result of L2 instruction in a tertiary Indonesian EFL context by comparing the presence of argument-counterargument features in the students' L1 and L2 essays. This quantitative study was conducted at a private Indonesian university, involving students from English Education (N=89) and Indonesian Language and Literature (N=100) study programs. The study found evidence of reverse transfer in the use of argument-counterargument structure among third-year English majors deemed to be skillful writers. However, the occurrence of it is not automatic, mediated by factors such as the writer’s writing proficiency, L2 proficiency, and perceived audience expectation. This finding shows that the reverse transfer of writing knowledge is dynamic and influenced by both the student’s writing ability development and L1 and L2 writing traditions.